(untitled) (Per Musi, 2021)
The historical performing styles in tango as a socio‐cultural construction give rise to the elaboration of the canon of the musical style that we know today. In this stylistic tradition, Aníbal Troilo is one of the relevant figures. In this work we analyze Troilo’s modes of temporal enunciation in order to find indicators of the construction of the temporal‐expressive patterns of his style. To do this we compare different interpretations of the tango Mi Refugio applying computer tools on manual beat annotations. We calculate tempo curves and compare them through correlation analysis and polynomial regression. Comparisons between different versions are interpreted through hermeneutical‐musical analysis. The results indicate a consistent use of temporal regulation patterns in Troilo’s phrasing at different expressive‐structural levels, beyond the variations in the musical surface of the arrangements. In addition, an increaseing‐decreacing resource was identified for articulatory purposes in the communication of the form.